AN ASSESSMENT OF THE ROLES OF THE SOCIAL NETWORK IN THE DEVELOPMENT OF THE TOURISM INDUSTRY IN BANGLADESH - Talukder, Mohammad Badruddoza; Bhuiyan, Md Lokman (International Journal of Business, Law, and Education, 2020)
Tourism is the fastest expanding business & service oriented industry in the world. The importance of social media is growing in the kingdom of the tourism business industry in Bangladesh. More and more researchers are undertaking studies in the areas of impact of social media on the tourism industry. The media is one of the most important tools for the tourism business. Social media is also can play a significant role in tourism advertising and helps the tourism service providers in focusing tourists and public. The aim of this study was to contribute in the tourism industry development in Bangladesh by providing factual information to relevant stakeholders and to understand the future role of social media in the years to come on the tourism so that it benefits the tourism industry and the tourists globally. To investigate the reasons behind tourism industry development, a survey conducted on 2000 respondents that include different professionals & non professionals. Most of the researchers have focused on the positive side of Social media contribution to develop tourism industry in Bangladesh.